Radiation effects on Marangoni convection over a flat surface with suction and injection - Abdul Hamid, Rohana; Md Arifin, Norihan; Nazar, Roslinda; Md Ali, Fadzilah (Universiti Putra Malaysia Press, 2011)
The radiation effect on a steady two-dimensional Marangoni convection flow over a permeable flat surface is studied numerically. The general governing partial differential equations are transformed into a set of two nonlinear ordinary differential equations by using unique similarity transformation. Numerical solutions of the similarity equations are obtained using the shooting method. Numerical results are obtained for the interface velocity and the surface temperature gradient as well as the velocity and temperature profiles for some values of the governing parameters. The results indicate that the heat transfer rate at the surface decreases as the radiation parameter increases. The effects of suction or injection parameter on the flow and heat transfer characteristics are discussed.